Anisotropic Grain Boundary Mobility in Undoped and Doped Alumina. Issue 5 (9th February 2014) - Akiva, Ran; Katsman, Alexander; Kaplan, Wayne D.; Rohrer, G.
<x xml:space="preserve">Abstract</x> The grain boundary mobility of polycrystalline alumina (α‐Al2O3), and the effective grain boundary mobility of the basal (0001) plane as it grew into polycrystalline alumina, was determined for undoped alumina, alumina doped with 23 ppm MgO, and alumina doped with 13 ppm CaO at 1600°C. Doping with MgO at a level below the solubility limit decreased the grain‐boundary mobility from 2.7 × 10−15 to 1.5 × 10−15 m2/s, and doping with CaO at a level below the solubility limit increased the mobility to 3.5 × 10−15 m2/s. For the undoped samples at 1600°C, the activation energy for the average grain boundary mobility was 372 ± 39 kJ/mol. The mobility of the (0001) plane growing into alumina doped with MgO at a level below the solubility limit decreased to 1.1 × 10−15 m2/s compared with the mobility of the (0001) plane growing into undoped alumina (2.5 × 10−15 m2/s), and the mobility of the (0001) plane growing into alumina doped with CaO (below the solubility limit) increased to 3.2 × 10−15 m2/s. The activation energy for the mobility of the (0001) plane was 483 ± 76 kJ/mol. Although a measured Ca excess of 2.6 Ca/nm2 at the boundary between the (0001) plane and CaO‐doped alumina is correlated with an increased mobility, the platelike morphology of CaO‐doped polycrystalline alumina is associated with an increased mobility of nonbasal planes.